Impact of state government political intefernce on financial autonomy of a local government in Nigeria - Bashir, Usman (2018)
Before the implementation of joint account system Zaria local government and others in Kaduna State access their monthly financial allocation directly from the federation account. With the implementation of joint account, Kaduna state government interfere in the administration of Zaria Local government which lead to controlling and lack of access to its allocation from federation account. Therefore this study attempt to investigate the responses of the people on the impact of state government political interference on the financial autonomy of Zaria local government, a phenomenology approach was used in this study and data were obtained from purposively selected informants using semi structure interviews. Thus, thematic analysis, informal discussions were employed in data analysis. The result shows that the constant access denying, deduction and controlling of local government funds in the name of state and local government joint account by the Kaduna State government resulted to inadequate financial resources which is responsible for the inability of the local government for regular payment of workers salary, deteriorated access roads and social insecurity, poor basic primary health care and educational system that lead to high infant mortality rate and increased in illiteracy level. The study recommends that only with the abolishing of state and local government joint account, Zaria local government would be able to achieve its quest for financial autonomy and improve the living condition of its local populace.